Bisnis Kerawang Gayo Menggunakan Cloud Computing Berbasis Android - Amna Amna; Rima Gemasih; Ira Zulfa (Elkom : Jurnal Elektronika dan Komputer, 2020)
Cloud computing is a technology that makes the internet a center for managing data and applications. With computer users are granted access (login). Cloud is a metaphor for the internet, as the cloud is often depicted in computer network diagrams. Gayo’s openwork cloud application is an android bases application that utilizes Cloud computing technology in the form of cloud Platform as a Service (SAAS) function as the main container or basis for running the system that will use in sales and providing notification services for the search for souvenirs typical of Takengon, namely Kerawang Gayo. Cloud computing is a technology that makes the internet a central storage server for managing data and information. This technology also allows users to freely manage and access information available on cloud storage which is of course connected to the internet network. This gayo filigree is now being created as a result of the home craft industry being embroidered on the cloth. The craft produces various types of souvenirs such as bags, key chains, women’s robes, men’s shirts, caps, bracelets, wallets, prayer mats, tablecloths, pillowcases, cellphone covers, and women’s and men’s traditional clothes, skirts, and scarves. Using the prototyping method is a software development method in the form of a physical working model of the system that functions as an early version of the system.